Cell-based immunotherapies for solid tumors: advances, challenges, and future directions - Ting Zhao; Jinping You; Congyue Wang; Bo Li; Yuhan Liu; Mingjia Shao; Wuyang Zhao; Chuang Zhou (Frontiers in Oncology)
Cell-based immunotherapies, including CAR-T, CAR-NK, and TCR-T therapies, represent a transformative approach to cancer treatment by offering precise targeting of tumor cells. Despite their success in hematologic malignancies, these therapies encounter significant challenges in treating solid tumors, such as antigen heterogeneity, immunosuppressive tumor microenvironments, limited cellular infiltration, off-target toxicity, and difficulties in manufacturing scalability. CAR-T cells have demonstrated exceptional efficacy in blood cancers but face obstacles in solid tumors, whereas CAR-NK cells offer reduced graft-versus-host disease but encounter similar barriers. TCR-T cells expand the range of treatable cancers by targeting intracellular antigens but require meticulous antigen selection to prevent off-target effects. Alternative therapies like TIL, NK, and CIK cells show promise but require further optimization to enhance persistence and overcome immunosuppressive barriers. Manufacturing complexity, high costs, and ensuring safety and efficacy remain critical challenges. Future advancements in gene editing, multi-antigen targeting, synthetic biology, off-the-shelf products, and personalized medicine hold the potential to address these issues and expand the use of cell-based therapies. Continued research and innovation are essential to improving safety, efficacy, and scalability, ultimately leading to better patient outcomes.